CHARACTERIZATION OF MONOHEADED TRYPSIN INHIBITORS FROM THE SEEDS OF ABELMOSCHUS MOSCHATUS L. - Kumar Dokka, Muni; K. P. J, Hemalatha; Davuluri, Siva Prasad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present study was to characterize the monoheaded trypsin inhibitors, Abelmoschus moschatus trypsin inhibitor-I (AMTI-I) and AMTI-II from the seeds of A. moschatus with respect to their specificity, mode of action, and active site residues. Methods: Standard methods were followed in determining inhibitory activities of monoheaded inhibitors. IC50 values and inhibitory constants (Ki) of AMTI-I and AMTI-II were determined. Studies on complex formation and chemical modification of inhibitors were performed. Results: AMTI-I and AMTI-II were found to be serpins, strongly active against trypsin, moderately active against porcine elastase, Staphylococcus aureus protease, and Aspergillus oryzae protease. AMTI-I and AMTI-II have shown non-competitive type of inhibition toward bovine trypsin with Ki values of inhibitors for trypsin found to be 0.25Â±0.02 nM and 0.22Â±0.06 nM, respectively. Complex studies revealed the formation of stable 1:1 complex of trypsin with both AMTI-I and AMTI-II. Chemical modification of the functional groups of the inhibitors by selective reagents indicated that arginine residues are essential for their trypsin inhibitory activities. Conclusion: Investigations on the specificity of protease inhibitors are important for understanding their physiological role, control mechanisms involved in the regulation of proteolysis in biological systems and mode of action.